Treatment of Far Lateral Lumbar disc Herniation Via a Minimally invasive Approach - Yasser Allam (Egyptian Spine Association, 2012)
Back Ground Data: Far lateral lumbar disc herniation is a unique entity. It needs special care in designing the best surgical approach. Many limited approached have been advocated. We report a case series treated by a minimally invasive approach. Purpose: to evaluate the efficacy and safety of minimally invasive approach in treatment of far lateral lumbar disc herniation. Study Design: Prospective analytic study. Methods: 25 patients suffering from far lateral disc herniation (extra-foraminal) were operated according to this technique. Through a small skin incision (1.5 cm), the paraspinal muscles are spread by dilators, until a working channel of 11 mm inner diameter and 14 mm outer diameter can be placed. All further steps are performed through this channel under illumination and control of the operating microscope. The mean follow up period was one year, and patients were evaluated by using the Visual Analogue Scale (VAS) and the Oswestry Disability Index (ODI). Results: The average surgical time was 49.2 minutes. The ODI improved from 29.96 (preoperative) to 12.12 (post-operative). The VAS of back pain improved from 6.24 (pre-operative) to 3.4 (post-operative).The VAS of leg pain improved from 7.2 (pre-operative) to 2.6 (postoperative). No intra-operative or early postoperative complications occurred. However, only one recurrence happened and could be treated by the same technique. Conclusion: The results from this small series seem to promise that this minimal invasive microscope assisted technique is a practical and valuable alternative to conventional techniques for the treatment of far lateral lumbar disc herniation. The main advantages include: minimal surgical trauma, no effect on the stability of the spine, rapid rehabilitation, short hospital stay and excellent cosmetic outcome. (2012ESJ018)